Analisis Faktor Yang Mempengaruhi Tercapainya On Time Performance Pada Kegiatan Transportasi Udara: Studi Pada Bandar Udara Internasional Ahmad Yani Semarang - Adenanthera Lesmana Dewa; Kirana Rara Ningrum; Lisda Rahmasari (Fakultas Ekonomi Universitas 45 Surabaya, 2021)
Currently, many companies in the service sector are competing to meet human needs and desires. Semarang Ahmad Yani International Airport is an example of a company that offers its services in the aviation sector. The purpose of this study was to determine the effect of flight schedules, human resources, landside capacity, and ground handling performance on the achievement of On time performance at Ahmad Yani International Airport, Semarang. The data was collected by using the method of observation, literature study, filling out questionnaires, and documentation. The analysis technique used is multiple linear regression with the help of SPSS V.25 program, the results are Y = 0.720 +0.213X1+0,304X2+0,234X3 + 0,230X4+µ. The results of multiple linear equations indicate that there is a positive influence between flight schedules on on time performance (t count 2,523 > t table 1,99547), human resources on on time performance (t count 2,515 > t table 1,99547), landside capacity on on time performance (t count 2,299 > t table 1,99547), ground handling performance on on time performance (t count 3,189 > t table 1,99547). The results of the regression test obtained the coefficient of determination (R square) of 0.649. This means that the flight schedule variable (X1), HR (X2) landside capacity (X3), and ground handling performance have a contribution of 64.9% in influencing on time performance (Y). While other factors that affect on time performance by 35.1%.